Strategy for science, technology and innovation development: analysis from approach perspective - Tuyen, Hoang Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The strategy for science, technology and innovation (STI) development acts as a public institution, a tool for serving state management and a basis for allocating resources for STI development. Not only on a national scale, the strategy for STI development is also very useful for the sectors/disciplines, organizations, enterprises, especially for those who want to have core capacity and technologies. Based on the theory of approaches in STI development, an analysis of experiences on approaches to development of STI strategies of selected countries, the article will give some suggestions for Vietnam in developing the STI strategy for the period of 2021-2030. Code: 17092801